Strengthening Pacifism through History Learning at Madrasah Aliyah in Aceh: A Critical Evaluation - Inayatillah, Inayatillah; Yussuf, Ahmad; Kurniawan, Ade; Hasnadi, Hasnadi (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
The study aims to describe the value of learning local history and the value of opposing violence to settle disputes as taught in Madrasah Aliyah Aceh, Indonesia, which has schools in Pidie, Banda Aceh, West Aceh, and East Aceh. The data were collected from the madrasah heads, history teachers, and school supervisors. The data were collected through interviews, observations, focus group discussions, and studied documents. The results showed that Madrasah Aliyah in Aceh has failed to achieve its obective due to several factors. History teachers follow the standard lesson plans without making the necessary modifications to include elements of pacifism. The students are not actively involved in the learning process and the classes are teacher-centered, thus not supporting higher-order thinking skills. Teachers show a lack of understanding in conducting question point analysis. The elements of pacifism is not sufficiently highlighted in the history classes, thus failing to make optimal use of instilling important social values in the students and use the history subject for character education. Teachers have different educational backgrounds and varying levels of pedagogic competence, thus requiring more specific guidance and training from Madrasah Aliyah Aceh to be able to render this promising approach to history instruction more successful in practice.